Perspectivism, animism and quimeras: a reflection on amerindian design systems as techniques for altering perception (2012)
This article explores how different formal techniques used by the Cashinahua and other “people with design” can be considered as “perspectival techniques”, meaning techniques enabling the onlooker to change point of view. I also consider the possibility of baptizing these design systems as “abstract chimeras”. I use chimera in the sense given to the term by Severi, calling attention to the tension between what is shown and what is hidden in an image. I argue that in the case of Amerindian design systems we are dealing with extremely minimalistic images, which suppose a real engagement of the act of seeing with the image. I show how different formal characteristics of the composition of the images constitute techniques for the focalization of the gaze, whose kinesthetic effect consists in projecting the onlooker into the graphic space, causing the opacity of the surface to disappear and producing movement and profundity in the perceptive space. The line produces the suggestion of transparency of the skin, produces pathways and opens towards the perception of figuration inside the frame of the patterned surface.